Pengaruh Jumlah Penduduk dan Pengangguran Terhadap Kemiskinan di Provinsi Jawa Barat Tahun 2018–2022 - Widiyarini, Widiyarini; Asikin, Iin; Septariani, Desy; Johan, Ria Susanti (JUDICIOUS, 2025)
This study aims to analyse the effect of population size and unemployment on poverty levels in West Java Province during the period 2018–2022. Using an associative quantitative approach with secondary data from the Central Statistics Agency, this study examines the relationship between variables using multiple linear regression analysis. The results indicate that population size has a negative and significant effect on poverty, while unemployment does not have a significant partial effect. However, when considered simultaneously, population size and unemployment have a significant effect on poverty levels. These findings have important implications for the formulation of more targeted regional development policies aimed at poverty alleviation.